Monetary policy and housing prices in an estimated DSGE for the US and the euro area - Matthieu Darracq Pariès; Alessandro Notarpietro (European Central Bank (ECB), 2008)
We estimate a two-country Dynamic Stochastic General Equilibrium model for the US and the euro area including relevant housing market features and examine the monetary policy implications of housing-related disturbances. In particular, we derive the optimal monetary policy cooperation consistent with the structural specification of the model. Our estimation results reinforce the existing evidence on the role of housing and mortgage markets for the US and provide new evidence on the importance of the collateral channel in the euro area. Moreover, we document the various implications of credit frictions for the propagation of macroeconomic disturbances and the conduct of monetary policy. We find that allowing for some degree of monetary policy response to fluctuations in the price of residential goods improves the empirical fit of the model and is consistent with the main features of optimal monetary policy response to housing-related shocks.
Keywords: E4; E5; F4; 330; Bayesian estimation; credit frictions; housing; new open economy macroeconomics; optimal monetary policy; Geldpolitik; Immobilienpreis; Dynamisches Gleichgewicht; Neue Makroökonomik offener Volkswirtschaften; Schätztheorie; EU-Staaten; USA